2013
DOI: 10.4338/aci-2012-09-ra-0034
|View full text |Cite
|
Sign up to set email alerts
|

Usability characteristics of self-administered computer-assisted interviewing in the emergency department

Abstract: SummaryObjective: Self-administered computer-assisted interviewing (SACAI) gathers accurate information from patients and could facilitate Emergency Department (ED) diagnosis. As part of an ongoing research effort whose long-range goal is to develop automated medical interviewing for diagnostic decision support, we explored usability attributes of SACAI in the ED. Methods: Cross-sectional study at two urban, academic EDs. Convenience sample recruited daily over six weeks. Adult, non-level I trauma patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…These results are consistent with those of prior studies of data entry using tablet computers, which found worse data accuracy in older individuals and differences based on race and prior technology use. 6,7 Fifty-one percent of older adults in the current study were willing to use a tablet, and many of those had difficulty providing correct responses, with 32% correctly answering all questions. Of participants with mild or no cognitive impairment, 45% were willing to try to use the tablet, and 32% answered all questions correctly.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with those of prior studies of data entry using tablet computers, which found worse data accuracy in older individuals and differences based on race and prior technology use. 6,7 Fifty-one percent of older adults in the current study were willing to use a tablet, and many of those had difficulty providing correct responses, with 32% correctly answering all questions. Of participants with mild or no cognitive impairment, 45% were willing to try to use the tablet, and 32% answered all questions correctly.…”
Section: Discussionmentioning
confidence: 90%
“…Level of formal education, which has been shown to affect performance on electronic questionnaires, was not assessed. 6,7 Study subjects were predominantly white, which may limit generalizability to more ethnically diverse populations. Delirium, 23,24 which may have been present in some participants and may have contributed to unwillingness or inability to use the tablet, was not assessed for.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we allowed patients to skip individual questions by pressing a next button. On average, the response times for our patient population exceeded those previously reported for a self-administered non-audio electronic survey system [15]; however, direct comparisons are complicated by differences in instruments, patient populations, and possibly network speed.…”
Section: Discussionmentioning
confidence: 51%
“…The behaviour of Mediktor in the classification of severity levels is close to what is expected with the percentage of hospital admission (Level 3: 76.5%, Level 4: 11.8% and Level 5: 11.8%). The scope of Mediktor in the collection of data is greater, so a different classification model is expected, although without statistically significant differences in this sample size based on a study that used case simulations [26] when not finding similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the original publication [12] it was not valued independently in the different levels of classification, so we did not have previous data of its possible applicability to the group of less complexity studied and, therefore, with lower forecast of need for hospital admission In our project we used a nurse to feed the system with the patient's answers and answer their questions, without interfering with the symptoms that the patient wanted to expose. Herrick et al (26), in a study on the usability of a self-administered questionnaire for emergency diagnosis, found that 86% did not require assistance. Those who needed help were older (54 ± 19) years.…”
Section: Discussionmentioning
confidence: 99%